Long-Term Limitation Effects of Se(VI), Zn(II), and Ni(II) on Start-Up of the Anammox Process Using Gel Carrier - Isaka, Kazuichi; Sugawara, Daichi; Yamazaki, Hiroshi; Kimura, Yuya; Osaka, Toshifumi; Tsuneda, Satoshi (Frontiers in Bioengineering and Biotechnology, 2022)
Anaerobic ammonia oxidation (anammox) bacteria are inhibited by heavy metals at high concentrations but require trace amounts of some heavy-metal elements for growth and activity maintenance. The present study evaluates the long-term limitation effects of Se(VI), Zn(Ⅱ), and Ni(Ⅱ) on the start-up period of an anammox reactor. To strictly limit the levels of heavy metals in the reactor, all tests used ultrapure water as the influent synthetic wastewater and all reactors were installed in a clean booth. The anammox biomass was maintained through the gel entrapment technique. In the absence of Se(VI) and Ni(Ⅱ), the anammox reactor start-up was 18.9 kg-N (m3-carrier d)−1 (nitrogen conversion rate (NCR) per gel carriers), indicating that Se(VI) and Ni(Ⅱ) are not required or need not be continuously added to maintain the anammox process. Under Zn(Ⅱ) limitation, the anammox process failed to start-up and the NCR tended to decrease rapidly. After readdition of 0.005 mg L−1 of Zn(II), the NCR did not decline further and instead partially recovered at a very slow rate. The NCR was completely recovered after adding 0.020 mg L−1 of Zn(Ⅱ). These results reveal that Zn(II) limitation seriously affects the start-up of the anammox process while Se(VI) and Ni(II) are not required or need not be continuously added to the anammox process.